(untitled) (Research, Society and Development, 2022)
Objective: To understand, based on narratives, the experiences of psychic suffering experienced by students at the Technology Center at the Federal University of Ceará. Method: This is a research with a qualitative approach and an exploratory and descriptive nature, carried out in eleven undergraduate courses in Engineering at the Technology Center of the Federal University of Ceará. Semi-structured interviews were carried out and a focus group was constituted. The narratives were organized in knots and analyzed based on Bardin’s discourse analysis. Results: 4 categories were formed from the ten nodes considered in the discourse analysis: Category 1: “grades”, “failure” and “stress”; Category 2: “teaching” and “relationship with teacher”; Category 3: “mental health”, “dropout”, “support” and “external support”; and Category 4: “being an engineering student”. Conclusion: It is necessary to propose preventive interventions, identification and care for the psychological distress of these students, in order to promote mental health and quality of life for students.